Efektivitas Media Pembelajaran Teori Sastra Berbasis Mobile Learning Berbantuan Aplikasi Inventor - Fina Hiasa; Emi Agustina; Supadi Supadi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to increase student motivation and learning outcomes in the Literary Theory course using mobile learning-based learning media assisted by the inventor application. Classroom action research using the descriptive method was carried out in two cycles. Data collection was carried out using test and non-test techniques. The results showed that the achievement targets were successfully obtained in Cycle II, namely 31% or as many as 10 students obtaining very good grades. The results of Cycle II increased compared to Cycle I, with very good grades only obtained by 7 students. In addition, the results of student responses in Cycles I and II also experienced a shift for the better. The average distribution of the percentages answered by students in Cycle II, namely Agree 66%, Quite Agree 32%, and Disagree 1.9%. From these results, it can be concluded that there is an increase in learning outcomes and student motivation in Literature Theory learning activities when using mobile learning-based learning media assisted by the inventor application.